Antagonizing L-type Ca2+ Channel Reduces Development of Abnormal Involuntary Movement in the Rat Model of L-3,4-Dihydroxyphenylalanine-Induced Dyskinesia - Schuster, Stefan; Doudnikoff, Evelyne; Rylander, Daniella; Berthet, Amandine; Aubert, Incarnation; Ittrich, Carina; Bloch, Bertrand; Cenci, M. Angela; Surmeier, D. James; Hengerer, Bastian; Bezard, Erwan (Biological psychiatry (1969), 2009)
Chronic L-3,4-dihydroxyphenylalanine (L-DOPA) treatment of Parkinson's disease (PD) leads to debilitating involuntary movements, termed L-DOPA-induced dyskinesia. Striatofugal medium spiny neurons (MSN) lose their dendritic spines and cortico-striatal glutamatergic synapses in PD and in experimental models of DA depletion. This loss of connectivity is triggered by a dysregulation of intraspine Cav1.3 L-type Ca2+ channels. Here we address the possible implication of DA denervation-induced spine pruning in the development of L-DOPA-induced dyskinesia. The L-type Ca2+ antagonist, isradipine was subcutaneously delivered to rats at the doses of .05, .1, or .2 mg/kg/day, for 4 weeks, starting the day after a unilateral nigrostriatal 6-hydroxydopamine (6-OHDA) lesion. Fourteen days later, L-DOPA treatment was initiated. Isradipine-treated animals displayed a dose-dependent reduction in L-DOPA-induced rotational behavior and abnormal involuntary movements. Dendritic spine counting at electron microscopy level showed that isradipine (.2 mg/kg/day) prevented the 6-OHDA-induced spine loss and normalized preproenkephalin-A messenger RNA expression. Involuntary movements were not reduced when isradipine treatment was started concomitantly with L-DOPA. These results indicate that isradipine, at a therapeutically relevant dose, might represent a treatment option for preventing L-DOPA-induced dyskinesia in PD.